KEDUDUKAN NOTARIS YANG MERANGKAP SEBAGAI DOSEN DAN MEMILIKI JABATAN STRUKTURAL DI PERGURUAN TINGGI - Kartini, Rosalina; Sesung, Rusdianto (Legality : Jurnal Ilmiah Hukum, 2017)
Characteristic of Notarial as an esoteric science brings consequence which makes this science cannot be taught to person who does not possess knowledge within this field.Â  In order to produce high quality candidates of notary public, Some University as educational agency of notarial science provides structural position for notarial practitioner to become lecturer in Notarial Master Program at the University. This approach is conducted to adjust between learning curriculum of notarial science and learning outcome of the graduates as notary public. But this approach is obstructed with rules that are enacted in Regulation of Notary Public (Undang-Undang Jabatan Notaris) which prohibit notary public to hold double positions as lecturer coupled with practitioner.